Childhood Vasculitis - Schnabel, Anja; Hedrich, Christian M. (Frontiers in Pediatrics, 2019)
The term vasculitis covers heterogeneous disorders that share the presence of inflammation of blood vessel walls. Immune cell infiltrates can vary significantly and involve granulocytes or mononuclear cells. Vasculitis can be a symptom of other underlying disorders or the underlying cause of organ specific or systemic disease. Classification of childhood vasculitis is based on clinic, the size of predominantly affected vessels, and the histopathology of inflammatory infiltrates. Timely and accurate diagnosis and (where necessary) treatment initiation determine disease progression and outcomes. In light of new developments and the identification of autoinflammatory conditions with vasculitis, new classification tools may be discussed.